Various answers to the skeptical argument - Ebner, Maria (Hybris, 2019)
The aim of this paper is to present various answers to the skeptical argument and propose an alternative solution. Suggested solution refers to the results of empirical research which lead to abandonment of entailment thesis concerning knowledge. My answer is contextualist inasmuch as it recognizes the existence of different concepts of knowledge. The applicability of these concepts depends on the situation; in a skeptical context the concept of knowledge is not accompanied by appropriate belief, and in ordinary contexts knowledge requires a belief of specific content.